The multidisciplinary fetal center: clinical expertise is only part of the experience. (17th April 2017) - Kett, Jennifer C.; Wolfe, Elana; Vernon, Margaret M.; Woodrum, David; Diekema, Douglas
Abstract: Aim: Multidisciplinary foetal centres have recently emerged in partnership with children's hospitals throughout the United States. The aim of this investigation was to describe the patient experience of pregnant women who were referred to our foetal centres for the evaluation of foetal congenital anomalies. Methods: A qualitative interview study of women referred to our foetal centres was conducted using semi‐structured telephone interviews. The data were coded and analysed using thematic networks analysis. Results: Six themes were identified (i) foetal centre evaluations had a far‐reaching impact on participants' lives, (ii) participants appreciated both expertise and support from providers, (iii) participants recognised the need to cope with uncertainty, (iv) participants sought additional support from multiple arenas, (v) participants specifically looked to the Internet for both information and support and (vi) participants had pre‐established views about pregnancy termination. Conclusion: Multidisciplinary foetal centres can provide a unified source of clinical expertise to women who are carrying a foetus with a suspected or identified congenital anomaly. Despite this diagnostic acumen, uncertainty is pervasive and patients seek support and additional information from a variety of other sources. This investigation is an important initial step in the evaluation of this emerging model of care.